2006
DOI: 10.1021/bi060304j
|View full text |Cite
|
Sign up to set email alerts
|

Stability of DNA Duplexes Containing GG, CC, AA, and TT Mismatches

Abstract: We employed salt-dependent differential scanning calorimetric measurements to characterize the stability of six oligomeric DNA duplexes (5'-GCCGGAXTGCCGG-3'/5'-CCGGCAYTCCGGC-3') that contain in the central XY position the GC, AT, GG, CC, AA, or TT base pair. The heat-induced helix-to-coil transitions of all the duplexes are associated with positive changes in heat capacity, DeltaC(p), ranging from 0.43 to 0.53 kcal/mol. Positive values of DeltaC(p) result in strong temperature dependences of changes in enthalp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
87
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 54 publications
15
87
0
3
Order By: Relevance
“…This is possibly due to hybridization of the P1 primer with the poly(A) tails of mRNAs via matched (A·T) and mismatched (A·G, A·C, and A·A) base pairs at 42°C during cDNA synthesis by AMV reverse transcriptase. In support of this possibility, previous studies have demonstrated and characterized A·G, A·C, and A·A mismatched base pairs (72)(73)(74)(75)(76)(77)(78). Further, the P1 primer may also randomly hybridize to RNAs (including mRNAs, rRNAs, and tRNAs) at 42°C during cDNA synthesis via matched (A·T and G·C) and previously demonstrated mismatched (G·T, G·A, A·C, T·C, G·G, A·A, T·T, and C·C) base pairs (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84).…”
Section: Resultsmentioning
confidence: 71%
“…This is possibly due to hybridization of the P1 primer with the poly(A) tails of mRNAs via matched (A·T) and mismatched (A·G, A·C, and A·A) base pairs at 42°C during cDNA synthesis by AMV reverse transcriptase. In support of this possibility, previous studies have demonstrated and characterized A·G, A·C, and A·A mismatched base pairs (72)(73)(74)(75)(76)(77)(78). Further, the P1 primer may also randomly hybridize to RNAs (including mRNAs, rRNAs, and tRNAs) at 42°C during cDNA synthesis via matched (A·T and G·C) and previously demonstrated mismatched (G·T, G·A, A·C, T·C, G·G, A·A, T·T, and C·C) base pairs (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84).…”
Section: Resultsmentioning
confidence: 71%
“…Changing the 5′ terminal base from a guanine to a cytosine in the SNP-containing target DNA relative to the fully complementary DNA target is the most destabilizing mismatch in terms of enthalpy42, reducing the T m by ∼2.6 °C. A similar change is observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with reports that incorporation of a mismatch into dsDNA has only a limited effect on the global conformation of a duplex. 36 …”
Section: Resultsmentioning
confidence: 99%